Invenções de arquitetura: uma análise de Instant City e Éden como propostas experimentais arquitetônicas - Silvério Neto, Adriane (2015)
This work investigates how the architectural language was addressed in conceptualists trends of the 1960s, with reference to two works: Eden and Instant City, respectively Helio Oiticica and Archigram. It is used as theme rationale, theory and application of Umberto Eco texts - mainly Estrutura Ausente - along with other writings and theorists who were selected, researched and aggregated for the enrichment of this research. In order to understand how to determine the architectural design proposal and the architectural structures in these works studied here, we intend to place the innovations of these productions in the midst of changes which then processed, questioning how they shook key points in the production of this group of British architects and Brazilian artist - especially as regards the relationship between spatial perception, the design paper to represent their propositions and architectural language to the art and post-modern architecture. Therefore, the project and the design will be addressed as the subject of research, as architectural language, analyzing the interests of their creators. Ultimately, this research aims to identify common standards and procedures and, according to the possible point as the drawing representations and architectural objects were employed. And yet, its importance to art and architecture. Paying attention in making a difference and behavior of proximity of objects of study adopted here: we believe the convergence point would be the interpretation of the fragmented architecture objects; and the point of difference would be the value assigned to the project as proposition for Eden and Instant City